2014
DOI: 10.1161/circulationaha.114.009683
|View full text |Cite
|
Sign up to set email alerts
|

PTP1b Is a Physiologic Regulator of Vascular Endothelial Growth Factor Signaling in Endothelial Cells

Abstract: Background— Regulation of vascular endothelial growth factor receptor-2 (VEGFR2) signaling is a control point that determines the extent of vascular tree formation. Recent studies demonstrated an important role played by VEGFR2 endothelial trafficking in control of its activity and suggested the involvement of a phosphotyrosine phosphatase 1b (PTP1b) in this process. This study was designed to define the role of PTP1b in endothelial VEGFR2 signaling and its role in regulation of angiogenesis and arteriogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 28 publications
4
91
1
Order By: Relevance
“…25 Similarly, mice with endothelial PTP1B deficiency also showed increased vascular endothelial growth factor signaling, together with increased angiogenesis and arteriogenesis in a model of hindlimb ischemia, although cardiac ischemia was not studied in this study. 26 In contrast, in this study, we found no change in cardiac capillary density or MRI-based LV perfusion at 4 months post-MI. Thus, although we cannot exclude that early changes in angiogenesis or perfusion may have occurred in our study, this would suggest that the reduced CHF severity that we observed is to a large extent independent of changes in cardiac angiogenic responses.…”
Section: Discussioncontrasting
confidence: 90%
“…25 Similarly, mice with endothelial PTP1B deficiency also showed increased vascular endothelial growth factor signaling, together with increased angiogenesis and arteriogenesis in a model of hindlimb ischemia, although cardiac ischemia was not studied in this study. 26 In contrast, in this study, we found no change in cardiac capillary density or MRI-based LV perfusion at 4 months post-MI. Thus, although we cannot exclude that early changes in angiogenesis or perfusion may have occurred in our study, this would suggest that the reduced CHF severity that we observed is to a large extent independent of changes in cardiac angiogenic responses.…”
Section: Discussioncontrasting
confidence: 90%
“…These data demonstrate that knockdown of PTP1B enhances the formation of new vessels in mouse aortic explants in a 3-dimensional gel-based environment. Along the same line with our findings, mice deficient in PTP1B in endothelial cells exhibited enhanced capillary growth in response to VEGF in matrigel implants (10). Moreover, PTP1B knock-out mice showed increased cardiac angiogenesis post myocardial infarction (27).…”
Section: Calpain/ptp1b Axis In Vegfr2 Regulation and Angiogenesissupporting
confidence: 89%
“…A main finding of this study is that PTP1B is a negative regulator of VEGF-induced angiogenesis in endothelial cells, consistent with the recently unraveled contribution of PTP1B in endothelial cell signaling (8,10,26). In a mouse hindlimb ischemic angiogenesis model, PTP1B expression and activity were increased (8).…”
Section: Calpain/ptp1b Axis In Vegfr2 Regulation and Angiogenesissupporting
confidence: 89%
See 2 more Smart Citations